Enclosure Fires of Single and Multi-Block propellant Charges - Mense, M.; Pizzo, Y.; Lallemand, C.; Sardoy, N.; Porterie, T.; Pouschat, P.; Porterie, B. (New Insights into Physical Science Vol. 12, 2021)
Charges of ammonium perchlorate (AP) - hydroxyl-terminated polybutadiene (HTPB)-aluminum (Al) solid propellant, in the form of one or several shaped blocks, are burned in an enclosure representative of an ammunition storage room onboard a warship. The amount of charge used ranges from 2 to 23 kg. the fire behavior and the thermal response of the enclosure are evaluated in terms of gas pressure and temperature, and wall heat flux and temperature. First, burn characteristics of three different shaped blocks are inferred from visible and infrared images. The rate of regression of the surface of the burning block is found to be nearly independent of the geometry of the burning block and of the ambient conditions; It is equal to 1.3 ± 0.1 mm/s, in accordance with the literature data for an AP/HTPB/Al-type propellant. The influence of enclosure confinement, wall insulation and water spray on fire consequences is also investigated. Some experimental data are used to validate a volumetric model developed by DGA TN. Agreement and discrepancies are discussed. Second, experimental data obtained using single and multi-block propellant loads are compared to highlight what might happen in the event of charge fragmentation. It is found that the combined action of the increase in exposed propellant surface area and the interaction between blocks leads to a significant increase in the burning rate, which in turn results in more severe fire consequences.